Chemsex as a temporal strategy: rethinking rush use in sexual behavior among Chinese urban MSM - Haohua Wang (Sexual Health, 2026)
Background This study examined how Chinese urban men who have sex with men use rush in sexual contexts to organize sexual encounters. Existing Chinese research has mainly discussed rush use in relation to HIV-related vulnerability, condomless sex and multiple partners. Less is known about how participants themselves understand its role in intimacy and everyday life. This study addresses that gap by analyzing rush use as a temporal strategy. Methods The study drew on life-story interviews with 24 men who have sex with men in four major Chinese cities. Participants had used rush in a sexual context within the previous 12 months. Interviews explored experiences of rush use, sexual settings, partner contexts, work schedules, family expectations and digital sexual practices. Data were analyzed through narrative reading and thematic coding, with attention to timing, sequence, duration, rhythm and return. Results Participants described rush as more than a way to intensify sexual pleasure. They used it to reorganize sexual time through five practices: accelerating sexual initiation, prolonging encounters, creating temporary ‘bubbles’ away from work and family pressure, synchronizing bodily rhythms in group sex, and deferring responsibilities linked to marriage, disclosure and the future. These practices enabled fragile moments of intimacy, but also produced vulnerabilities, including compressed safety negotiation, fatigue, anxiety, exclusion, guilt and the return of everyday obligations. Conclusions Rush use among Chinese urban men who have sex with men should be understood not only through pleasure or risk, but also through its role in reshaping the temporal organization of intimacy. The study extends sexualized substance use research and queer temporality scholarship by showing how timing, pace, duration, and return shape risk, consent, care and aftercare. Sexual health and harm reduction approaches should therefore consider the temporal pressures under which sexual decisions are made.